The role of regional health systems on the waiting time inequalities in health care services: Evidences from Italy. (August 2021) - Landi, Stefano; Ivaldi, Enrico; Testi, Angela
Inequalities in effective access to healthcare are present among countries and within the same country. Despite in Italy exist the principle of equity in access to health system, there are evidence of different access rates in the form of unequal waiting time within the country. Waiting times are an instruments to ration healthcare services dealing with resource scarsity. Theoretically, it is a fair tool because waiting times should depend only on health needs and not on the ability to pay. However, a growing literature has pointed out that belonging to a particular socioeconomic status leads to waiting times inequalities for healthcare services. Many countries have socioeconomic disparities among regions, and healthcare organizations need to take into account these differences. The increasing power of Regional Health Authorities in decentralized health systems, as in the case of Italy, has generated different organizational ways to provide health care, possibly leading to different access rates in the form of unequal waiting time within the country. This paper aims to understand if the administrative area (Regional Health Authorities) in charge of health services affects waiting times lowering or strengthening health care access inequalities. Using a series of logistic regression models, this work suggests the presence of two vectors: socioeconomic inequalities and regional inequalities. Health organizations need to implement different kinds of answers for each vectors of inequalities.